The Impact of Digital Stress on Journalists: Challenges and Facing Them in the Digital Media Era - Bakar, Bakar; Harjono, Hary Soedarto; Sofyan, Sofyan (Program Magister Teknologi Pendidikan Universitas Jambi, 2025)
The rapid advancement of information and communication technologies in the Society 5.0 era has significantly transformed the operations of journalists, introducing both opportunities and challenges. One major challenge is digital stress, which arises from constant connectivity and excessive use of digital tools. This study examines the impact of organizational innovation, work climate, journalist ability, and performance on digital stress experienced by journalists. A quantitative research approach was employed, using a structured questionnaire to collect data from journalists in Jambi, Indonesia. The survey measured variables such as digital stress, work climate, organizational innovation, journalist skills, and performance, with the data analysed using SPSS software. The findings indicate that organizational innovation and work climate significantly influence digital stress, with a supportive organizational environment and a positive work climate acting as mitigating factors. However, journalist ability and performance were found to have no significant effect on digital stress. The regression model explained 54.3% of the variance in digital stress, emphasizing the importance of organizational factors in reducing stress. The study underscores the need for media organizations to foster an adaptive, balanced digital work environment by implementing mental health strategies, promoting digital resilience training, and setting clear work-life boundaries. These actions are crucial for improving the well-being and performance of journalists in an increasingly digitalized media landscape.